Bilirubin: An Endogenous Molecule with Antiviral Activity in vitro - Santangelo, Rosaria; Mancuso, Cesare; Marchetti, Simona; Di Stasio, Enrico; Pani, Giovambattista; Fadda, Giovanni (Frontiers in Pharmacology, 2012)
Bilirubin-IX-alpha (BR) is the final product of heme metabolism through the heme oxygenase/biliverdin reductase (HO/BVR) system. Previous papers reported on the microbicidal effects of the HO by-products biliverdin-IX-alpha, carbon monoxide and iron, through either direct or indirect mechanisms. In this paper the evidence of a virucidal effect of BR against human herpes simplex virus type 1 (HSV-1) and the enterovirus EV71 was provided. Bilirubin-IX-alpha, at concentrations 1-10 µM, close to those found in blood and tissues, significantly reduced HSV-1 and EV71 replication in Hep-2 and Vero cell lines, respectively. Bilirubin-IX-alpha inhibited viral infection of Hep-2 and Vero cells when given 2 hours before, concomitantly and 2 hours after viral infection. Furthermore, BR retained its antiviral activity even complexed with a saturating concentration of human serum-albumin. Moreover, 10 µM BR increased the formation of nitric oxide and the phosphorylation of JNK in Vero and Hep-2 cell lines, respectively, thus implying a role of these two pathways in the mechanism of antiviral activity of the bile pigment. In conclusion, these results support the antiviral effect of BR against HSV-1 and enterovirus in vitro, and put the basis for further basic and clinical studies to understand the real role of BR as an endogenous antiviral molecule.